Palliative care nurses’ experiences of stress, anxiety, and burnout: A thematic synthesis - Clayton, Malcolm; Marczak, Magda (Palliative & supportive care, 2023)
This systematic literature review aimed to critically appraise empirical evidence investigating palliative care (PC) nurses' experiences of stress, anxiety, and burnout. Six databases (PsycINFO, MEDLINE, Scopus, CINAHL, PubMed, and Web of Science) covering literature within psychology, medicine and healthcare, and social sciences were searched from inception until December 2020. Studies were eligible if they included qualitative literature reporting on experiences of nurses working in a PC setting of stress, anxiety, or burnout, and were published in English. Eighteen studies satisfied the review's inclusion criteria and were considered relevant to the review aims. Critical appraisal was undertaken using the Critical Appraisal Skills Programme Qualitative Checklist. Thematic synthesis identified three main themes: , , and . The findings suggested that stress, anxiety, and burnout are deeply personal feelings experienced by nurses both on an emotional and physical level. Additionally, PC nurses' experiences can differ in meaning and strength depending on their relationships with patients, patients' families, and colleagues. The synthesis highlighted that PC nurses' experiences are complex, encompassing clinical and organizational challenges, and the personal impact their work has on them. Having a greater understanding of the factors that contribute to PC nurses' experiences may help in PC nurses' core training and continuing professional education, as well as the provision of effective supervision and staff support.